Improved Production Performance and Health Status with Winter Mushroom Stem (Flammulina velutipes) in Laying Chicken: Review - Mahfuz , S.U.; Hui, Song; Zhongjun, Liu (International Journal of Poultry Science, 2017)
This study was conducted to represent the role of Flammulina velutipes stem in laying hen ration for improving laying performances and health status of layer chicken. Flammulina velutipes is one of the most popular edible mushroom in Asian countries and known as winter mushroom. Inclusion of Flammulina velutipes stem (FVS) in layer diets is the most effective supplement in order to improve laying performance, egg quality, intestinal morphology, cecal microflora and excreta composition. It has been reported that FVS in laying hen could improve laying performance and egg quality including Feed Conversion Ratio (FCR), egg mass, egg size, egg yolk cholesterol and yolk fatty acid. Flammulina velutipes stem can change small intestinal morphology that might help to increase nutrient absorption in chicken. Flammulina velutipes stem also reported on controlling pathogenic bacteria as well as increasing beneficial bacteria in cecum to keep sound gut health in layer chickens. Flammulina velutipes stem had indirect effect on suppression of ammonia gas in feces by reducing moisture content in feces. Therefore supplementation of winter mushroom stem could be useful strategy to improve laying performance, egg quality and sound gut health in layer.